Pengembangan Media Permainan Card Brain Scramble pada Materi Ikatan Kimia untuk Meningkatkan Gaya Kognitif Reflektif dan Hasil Belajar - Priyatmo, Yudhi; Danial, Muhammad; Herawati, Netti (Program Pasca Sarjana UNM, 2020)
This study is a development research which aims at developing CBS (Card Brain Scramble) game media on chemistry bond material to improve cognitive reflective style and learning outcomes which are valid, practical and effective to be applied. The development model used in this study referred to Hannafin and Peck’s development model, which consisted of several stages, namely need analysis stage, design making stage, development stage, and implementation stage. The learning media developed is CBS game media, then validated by two experts. After the validation, the tried out was conducted on the media which was conducted at MAN 3 Makassar in grade X MIPA with the total of 30 students. The results of the study reveal that the CBS game media which had been developed and validated indicate that the mean score is 3.65 with valid criteria. The CBS game media is stated as practical and effective because the practical test based on students' response on the utilization of CBS game media obtains 82.84% with the mean score of 3.31 which is in high level. The CBS game media also meets the effective criteria with the following results: (1) the improvement of cognitive reflective style of students is from 70.88% to 80.27%, (2) the learning outcomes meet the effective criteria which obtains from the mean score of 61% to 80.16%, whereas, the improvement of learning outcomes based on N-gain test is 0.49 which is moderate criteria. Therefore, the result of the study shows that the product of CBS game media developed is categorized as valid, practical, and effective.